Civil Society Experiences of Migrants Under International Protection and Temporary Protection: The Case of Türkiye - Melek Zubaroğlu Yanardağ; Mehmet Ateş (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In the context of irregular migration waves to Türkiye, in addition to the basic needs of migrants, their needs for representation and self-advocacy have also come to the fore. This situation has led to an increase in the number of civil society organizations established by migrants. The main purpose of this research is to examine the experiences of the migrants in civil society and to reveal how they engage in activities and practices, especially in terms of solidarity and self-advocacy. Within the scope of this qualitative study conducted within the framework of the phenomenological approach, interviews were conducted with 32 immigrants involved in migrant civil society organizations using an in-depth interview technique through a semi-structured interview form. In line with the interviews; it was seen that civil society organizations enable migrant individuals to participate effectively in social life and benefit from rights and services. In addition, it can be said that it is at an important point in terms of protecting social health by enabling individuals to interact with their environment and to be in a state of social well-being. On the other hand, it has been revealed that non-governmental organizations act as implementers of the services provided by public institutions and organizations or as a bridge for the services provided to reach individuals. In line with the findings of the research, it is aimed to ground the relationship between migration and NGOs and to contribute to the development of this field in the future.